Study Additions Sugar Factory Waste On Inorganic Fertilizers Against Seeds Productivity and Sugarcane Farming On dry land - Budi Utomo; Didit Setyaaji (Faculty of Agriculture, Merdeka University Surabaya, 2020)
The purpose of this study include: (1) Discover the difference in growth of seedlings of sugarcane in dry land with the use of inorganic fertilizer and the addition of sugar factory waste. (2) Know the difference analysis of farming and productivity of seeds cane on dry land with the use of inorganic fertilizer and the addition of sugar factory waste. (3) Determine the cost efficiency effort seeds cane on dry land by using inorganic fertilizer and the addition of sugar factory waste. (4) Determine the feasibility of sugarcane seeds business in dry land by using inorganic fertilizers and adding sugar factory waste.The analysis used in this study were: (1) Analysis Comparison of Growth using tabulation the data. The results showed differences in the results of production between three treatments, namely : Treatment of first use of NPK fertilizer 600 kg/ha and ZA 400 kg/ha showed yields 62 tons/ha while both use treatment NPK 600 kg/ha and ZA 400 kg/ha plus 2.5 tons/ha cut shows 63.6 tons/ha yield and the third treatment with NPK fertilizer dosage 300 kg/ha and ZA 200 kg/ha plus 2.5 tons/ha cut show 60.2 tons/ha yield. (2) Cost Analysis of farming and productivity by calculating the results of crop production using a system of tile on the treatment Into two with total cost of Rp. 3,842,353 and get the production of sugarcane seedlings of 63.6 tons/ha with an income of Rp. 610,114 (3) Analysis of the efficiency of businesses using the calculation of Revenue and Cost Ratio, the results obtained that treatment of three doses of NPK fertilizer 300 kg/ha and ZA 200 kg/ha with added 2.5 tonnes of sugar factory waste/hectare produce efficiency better business value The highest R/C ratio is 1.19. (4) Analysis of feasibility level of the business efficiency by calculating Benefit and Cost Ratio, results were obtained that the dosage of NPK fertilizer 300 kg/ha and ZA 200 kg/ha with added 2.5 tonnes of sugar factory waste/hectare produced level of feasibility of the highest value of B/C Ratio of 1.18.